Implementasi Bauran Pemasaran Sebagai Strategi Pemasaran Jasa Pendidikan - Erah Juraerah; Anis Fauzi; Supardi Supardi (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2024)
Educational institutions must now compete with other educational institutions to provide the best and most potential educational services and programmes. This study aims to investigate the use of marketing mix in marketing educational services at SMK Bismillah. In this study, data were collected using a descriptive qualitative approach, including observation, interviews, and documentation at the research location. After that, the data collected was tested for validity, namely by credibility test, transferability test, dependability test, and confirmability test. Data analysis uses data reduction, data presentation/display, and data verification (conclusions drowing/verifying). The results showed that 1) SMK Bismillah has successfully implemented an educational services marketing strategy using the marketing mix. This can be seen from the application of the seven parts of the marketing strategy, namely Strategy Product, Strategy Price, Strategy Place, Strategy Promotion, Strategy People, Strategy Physical Evidence, and Strategy Process. 2) Supporting factors for the implementation of the marketing mix of educational services marketing strategies at SMK Bismillah include Product strategies that rely on superior competencies, curriculum alignment with the world of work, and excellence and output from the majors at SMK Bismillah are strong supporting factors in attracting prospective students. In the aspect of human resources, SMK Bismillah has qualified and qualified educators and education personnel, so as to provide good education and in accordance with the needs of students. SMK Bismillah also ensures the use of a curriculum that complies with national standards and recommendations from the Ministry of National Education. Overall, SMK Bismillah has been successful in implementing educational services marketing strategies through a diverse and effective marketing mix.